За совладетелството на Деметриј II - Пановски, Стефан; Саракински, Војислав (Институт за национална историја, Скопје, 2019)
The aim of this paper is to review once more the evidence for the alleged co-regency of Gonatas and Demetrios II, as well as the interpretations offered by modern historians. While it is accepted that, considering all the evidence, the theories of both R. M. Errington and E. Grzybek are untenable, it is maintained that contrary to the opinion of a number of historians, the question is still far from settled. The contradictions in the sources remain unresolved, and most of the offered explanations are unconvincing or at the very least hypothetical, which is why the firm stance on the issue taken by some researchers (whether for or against a co-regency) seems unfounded. Considering the scarcity and the contradicting nature of the available evidence, a definitive solution of the issue remains impossible until a new piece of information presents itself.
Keywords: Demetrios Poliorketes, Demetrios II, Antigonos Gonatas, co-regency